DNGR-1 limits Flt3L-mediated antitumor immunity by restraining tumor-infiltrating type I conventional dendritic cells - Ignacio Melero; Ruth Conde-Garrosa; David Sancho; Santos Mañes; Alfonso R Sanchez-Paulete; Francisco J Cueto; Carlos del Fresno; Paola Brandi; Alexis J. Combes; Elena Hernández-García; Michel Enamorado; Christian P Bromley; et al. (Journal for ImmunoTherapy of Cancer)
Background Conventional type 1 dendritic cells (cDC1s) are central to antitumor immunity and their presence in the tumor microenvironment associates with improved outcomes in patients with cancer. DNGR-1 (CLEC9A) is a dead cell-sensing receptor highly restricted to cDC1s. DNGR-1 has been involved in both cross-presentation of dead cell-associated antigens and processes of disease tolerance, but its role in antitumor immunity has not been clarified yet.Methods B16 and MC38 tumor cell lines were inoculated subcutaneously into wild-type (WT) and DNGR-1-deficient mice. To overexpress Flt3L systemically, we performed gene therapy through the hydrodynamic injection of an Flt3L-encoding plasmid. To characterize the immune response, we performed flow cytometry and RNA-Seq of tumor-infiltrating cDC1s.Results Here, we found that cross-presentation of tumor antigens in the steady state was DNGR-1-independent. However, on Flt3L systemic overexpression, tumor growth was delayed in DNGR-1-deficient mice compared with WT mice. Of note, this protection was recapitulated by anti-DNGR-1-blocking antibodies in mice following Flt3L gene therapy. This improved antitumor immunity was associated with Batf3-dependent enhanced accumulation of CD8+ T cells and cDC1s within tumors. Mechanistically, the deficiency in DNGR-1 boosted an Flt3L-induced specific inflammatory gene signature in cDC1s, including Ccl5 expression. Indeed, the increased infiltration of cDC1s within tumors and their protective effect rely on CCL5/CCR5 chemoattraction. Moreover, FLT3LG and CCL5 or CCR5 gene expression signatures correlate with an enhanced cDC1 signature and a favorable overall survival in patients with cancer. Notably, cyclophosphamide elevated serum Flt3L levels and, in combination with the absence of DNGR-1, synergized against tumor growth.Conclusion DNGR-1 limits the accumulation of tumor-infiltrating cDC1s promoted by Flt3L. Thus, DNGR-1 blockade may improve antitumor immunity in tumor therapy settings associated to high Flt3L expression.